Understanding the Role of Psychological Capital in Humorous Leadership-Employee Creativity Relations - Li, Zhengwei; Dai, Lihua; Chin, Tachia; Rafiq, Muhammad (Frontiers in Psychology, 2019)
This paper aims to examine how humorous leadership enhances employee workplace creativity from a novel angle of employee psychological capital (EPC). This study also explores the moderating roles of supervisor–subordinate dyadic tenure and work autonomy in the proposed model. Data from a sample of 355 supervisor-subordinate dyads working in an information technology enterprise in the People’s Republic of China were used to test the assumed moderated mediation model. The results indicate the positive relationship between humorous leadership and employee workplace creativity, which is partially mediated by EPC. Moreover, work autonomy significantly moderates the relationship between EPC and employee creativity. Humorous leadership drives creativity among subordinates; this can have a significant effect on the extra-role behavior of subordinates, leading to workplace creativity. The deliberate establishment of a humorous image by leaders may encourage subordinates to achieve creative goals. Combined with traditional management practices that emphasize the supportive behaviors of leaders, leaders can use humor to provide an open and friendly atmosphere for employees, thereby encouraging creativity in the workplace. Organizations should also place greater emphasis on employee work autonomy, allowing employees flexibility on when and how they do their job; this could enhance the positive impact of other factors on employee workplace creativity. These findings carry implications for research on humorous leadership, EPC, and creativity.